INFORMATION OVERLOAD AT MAJOR CONFERENCES AND ITS IMPACT ON SIMULTANEOUS INTERPRETING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Major international conferences play a crucial role in the exchange of knowledge across linguistic and cultural boundaries. However, the rapid growth of information density, accelerated speech delivery, and the extensive use of multimedia presentations have created conditions of information overload. This phenomenon poses significant challenges for simultaneous interpreters, whose task requires the real-time processing and reformulation of complex information. The present article examines the nature of information overload in major conference settings and analyzes its impact on the quality, accuracy, and sustainability of simultaneous interpreting. The study highlights the cognitive and professional consequences of excessive information flow and emphasizes the importance of structured conference design, adequate preparation, and technological support. By addressing information overload as a systemic issue, this article contributes to a deeper understanding of interpreter performance in highdemand multilingual environments and proposes practical solutions to improve communication effectiveness.